Complete remission of recurrent gastric cancer in a young female patient through CLDN18.2-targeted therapy (LM302) and metastatic ovarian tumor resection: a case report of refractory disease overcoming chemotherapy and immunotherapy resistance - Muyang Chen; Tongshan Wang; Anpeng Wang; Hao Zhang (Frontiers in Oncology)
Young patients with recurrent, metastatic gastric cancer (GC) resistant to chemotherapy and immunotherapy have poor outcomes and limited treatment options. CLDN18.2 has emerged as a promising target in GC. We report the case of a 35-year-old female who experienced recurrence with bilateral ovarian and lymph node metastases 16 months after radical gastrectomy and adjuvant chemotherapy. Multiple therapies failed, and CLDN18.2 expression was suspected. She enrolled in a Phase I/II trial of LM302, a CLDN18.2-targeted antibody-drug conjugate, receiving eight cycles. Imaging showed significant regression of lymph node lesions and stable ovarian metastases. In April 2024, she underwent laparoscopic resection of the ovarian tumors, with pathology confirming no residual disease. As of March 2025, she remains disease-free with excellent performance status. This case illustrates that CLDN18.2-targeted therapy combined with surgery may offer curative potential in refractory GC and highlights the importance of biomarker-driven precision medicine.